Pemetaan Pusat Kesehatan Masyarakat (Puskesmas) Di Surabaya Selatan Menggunakan Software Arcgis - Anwar, Muhammad Nuril (Universitas Negeri Surabaya, 2023)
Puskesmas must be established in each sub-district that meets the requirements for location, building, infrastructure, equipment, and personnel. Location requirements which include geographical aspects, accessibility for transportation routes, land contours, parking facilities. Therefore, with the mapping of basic Puskesmas based on Geographic Information Systems, the end result is a map of the distribution of Puskesmas, which can provide convenience to the government in planning and monitoring regarding information about Puskesmas and the location of the location of the Puskesmas that we want to know, as well as recommendations to related parties if they want to build a Puskesmas so that attention in equity so that health services in South Surabaya are better. This study uses the nearest neighbor analysis method with ArcGis 10.8 software to determine distribution patterns. The results of this study showed that the distribution pattern of health centers in the South Surabaya area was included in the dispersed pattern category, mapping the location of health facilities in the South Surabaya area there were 16 health centers that were spread evenly in each sub-district, the range of services from health centers in the High category was that the area It is within reach of 3000 m.